The impact of insertion sequences on bacterial genome plasticity and adaptability. (2nd November 2017) - Vandecraen, Joachim; Chandler, Michael; Aertsen, Abram; Van Houdt, Rob
Abstract: Transposable elements (TE), small mobile genetic elements unable to exist independently of the host genome, were initially believed to be exclusively deleterious genomic parasites. However, it is now clear that they play an important role as bacterial mutagenic agents, enabling the host to adapt to new environmental challenges and to colonize new niches. This review focuses on the impact of insertion sequences (IS), arguably the smallest TE, on bacterial genome plasticity and concomitant adaptability of phenotypic traits, including resistance to antibacterial agents, virulence, pathogenicity and catabolism. The direct consequence of IS transposition is the insertion of one DNA sequence into another. This event can result in gene inactivation as well as in modulation of neighbouring gene expression. The latter is usually mediated by de-repression or by the introduction of a complete or partial promoter located within the element. Furthermore, transcription and transposition of IS are affected by host factors and in some cases by environmental signals offering the host an adaptive strategy and promoting genetic variability to withstand the environmental challenges.